HVEM and CD160: Regulators of Immunopathology During Malaria Blood-Stage - Muscate, Franziska; Stetter, Nadine; Schramm, Christoph; Schulze zur Wiesch, Julian; Bosurgi, Lidia; Jacobs, Thomas (Frontiers in Immunology, 2018)
CD8+ T cells are key players during infection with the malaria parasite Plasmodium berghei ANKA (PbA). While they cannot provide protection against blood-stage parasites, they can cause immunopathology, thus leading to the severe manifestation of cerebral malaria. Hence, the tight control of CD8+ T cell function is key in order to prevent fatal outcomes. One major mechanism to control CD8+ T cell activation, proliferation and effector function is the integration of co-inhibitory and co-stimulatory signals. In this study, we show that one such pathway, the HVEM-CD160 axis, significantly impacts CD8+ T cell regulation and thereby the incidence of cerebral malaria. Here, we show that the co-stimulatory molecule HVEM is indeed required to maintain CD8+ T effector populations during infection. Additionally, by generating a CD160-/- mouse line, we observe that the HVEM ligand CD160 counterbalances stimulatory signals in highly activated and cytotoxic CD8+ T effector cells, thereby restricting immunopathology. Importantly, CD160 is also induced on cytotoxic CD8+ T cells during acute Plasmodium falciparum malaria in humans. In conclusion, CD160 is specifically expressed on highly activated CD8+ T effector cells that are harmful during the blood-stage of malaria.